Driving SMEs' performance in South Africa: Investigating the role of performance appraisal practices and managerial competencies - Nhamo Mashavira; Sevias Guvuriro; Crispen Chipunza (Journal of Risk and Financial Management, 2022)
Managerial competencies and performance appraisal practices are often ignored when considering the performance of Small-to-Medium Enterprises (SMEs). Yet, these competencies and practices are fundamental for the survival of the SMEs. SMEs are critical for economic growth and job creation in many economies. The current study sought to establish whether managerial competencies and performance appraisal practices correlate with SMEs' performance in South Africa. Firm performance was measured using two variables: innovation and return on investment (ROI). The study adopted a structural equation modelling analytical approach. Interpersonal competencies were found to be a significant factor of managerial competencies, but conceptual and political competencies were not. The study also found that managerial competencies, and not performance appraisal practices, significantly correlated with both innovation and ROI. The study recommends that performance appraisal practices be tailored to suit SMEs in the developing countries context.
Keywords: 650; business performance; managerial competencies; performance appraisal; SMEs; South Africa